A Note on the Impact of the Canada-India Diplomatic Standoff on the Performance of Canadian Mutual Funds Investments in India - Pratima, F N U; Nippani, Srinivas; Phan, Hanh (Journal of Accounting and Finance, 2024)
On June 18, 2023, Mr. Hardeep Singh Nijjar, a Canadian citizen of Indian origin, was killed in Canada. On September 18, 2023, the Canadian Prime Minister, Mr. Justin Trudeau, accused the Indian Government of involvement in killing Mr. Nijjar in the Canadian Parliament. This accusation preceded and succeeded by other events, led to a significant diplomatic standoff that is still ongoing. We examine the impact of this event chain on the performance of daily returns of mutual funds based in Canada that are predominantly invested in Indian securities. Our results, controlled for general stock market returns, fund size, expense ratio, and interest rates, indicate that the events negatively impacted fund performance. Our study adds to the existing literature on the benefits of international diversification of mutual funds in disconnected markets. The findings of this paper suggest that political discord between two distinct and unrelated economies may impact profits and negate the advantages of international diversification. Our study is significant to professionals, particularly mutual fund managers, as it demonstrates the role of two countries’ political ties in affecting mutual fund returns.